(untitled) (REMUNOM, 2025)
This article focuses on mediation and conciliation in divorce proceedings, highlighting how these practices can contribute to the debureaucratization of private law. Given the slowness and excessive formality that still characterize many divorce cases in Brazil, it is essential to understand how alternative dispute resolution methods—such as mediation and conciliation—can make the process faster, more effective, and less distressing. The aim of this research is to demonstrate how these consensual methods help reduce judicialization and rationalize the justice system by promoting consensual, less traumatic, and more economically viable solutions to divorce-related conflicts. It also addresses the factors contributing to the bureaucratization of private law and the negative impacts of this reality on access to justice. The methodology used is qualitative, with a legal-deductive approach, through the analysis of legislative developments—especially Law No. 13,140/2015 and the 2015 Code of Civil Procedure—relevant legal doctrine, established case law, and the benefits of out-of-court settlements as a legitimate means of promoting social peace. The study concludes that mediation and conciliation, beyond being procedural techniques, restore agency to the parties and prioritize dialogue, thus fostering a faster and more accessible justice system.